2002
DOI: 10.1002/bsl.476
|View full text |Cite
|
Sign up to set email alerts
|

The psychology of telling murder stories: do we think in scripts, exemplars, or prototypes?

Abstract: According to the story model of Pennington and Hastie, jurors collect information at trial and modify it with general knowledge to create case stories. Schank and Ableson argue that human memory is organized to tell and understand stories. However, Finkel and Groscup questioned the use of manipulated, experimenter-constructed narratives to demonstrate the existence of multiple prototypical crime stories. We interviewed 76 jury eligible, death qualified citizens and asked them to imagine a first-degree murder s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…In fact, multiple schemas exist in criminal cases involving insanity (Skeem & Golding, 2001), murder (Wiener, Richmond, Seib, Rauch, & Hackney, 2002), rape (Ryan, 1988), assault, burglary, and kidnapping (V.L. Smith, 1991).…”
Section: Legal Schemas and Expectationsmentioning
confidence: 99%
“…In fact, multiple schemas exist in criminal cases involving insanity (Skeem & Golding, 2001), murder (Wiener, Richmond, Seib, Rauch, & Hackney, 2002), rape (Ryan, 1988), assault, burglary, and kidnapping (V.L. Smith, 1991).…”
Section: Legal Schemas and Expectationsmentioning
confidence: 99%
“…Because of this, jurors in rape or sexual assault cases are likely to draw on their existing knowledge or cognitive schemas to interpret what happened and how blame should be apportioned (Ellison & Munro, 2010; Pennington & Hastie, 1992). In generating these accounts, research has repeatedly demonstrated that people are influenced by schemas, which encompass both crime prototypes (Finkel & Groscup, 1997; Smith, 1991; Wiener, Richmond, Seib, Rauch, & Hackney, 2002)—cognitive representations of the typical or ideal features present in a particular crime—and stereotypes—simplified evaluative cognitive representations of the people involved in the crime. It is therefore critical to understand how jurors use these schemas to interpret information and form impressions about the blameworthiness of the defendant and the complainant.…”
mentioning
confidence: 99%
“…Studies that have measured schema have used qualitative methods initially to identify schema domain and elements. Several have used traditional prototype methodology , asking respondents to picture a type of person/situation in their mind and then describe characteristics of the person/situation in detail (Skeem & Golding 2001; Weiner, Richmond, Seib, Rauch & Hackney, 2002). Thought-listing techniques, another approach to identifying cognitive structures (Cacciopo, vonHippel & Ernst 1997) ask respondents to list their thoughts about a real or hypothetical experience or anticipated event.…”
Section: Introductionmentioning
confidence: 99%
“…Conover and Feldman (1984) used this method to examine how people organize political beliefs and found support for both a schematic model of political beliefs and their strategy for studying schematic knowledge. Studies have applied cluster analysis (Lurigio & Carroll, 1985;Skeem & Golding,2001; Weiner, et al, 2002) and/or factor analytic techniques (Skeem & Golding, 2001; Conover & Feldman , 1984) to rated item data to identify and compare cognitive representations across groups of people. The evidence here suggests that groups of people with more shared and repeated experiences of a subculture (Harris, 1994), such as probation officers (Lurigio & Carroll, 1985), have more efficient coalescence in categories of schema than in a broader population with a more diffuse and limited experience base, such as jurors (Skeem & Golding, 2001).…”
Section: Introductionmentioning
confidence: 99%